Sox-9 and cDachsund-2 expression in the developing chick telencephalon. - Szele, F; Chin, H; Rowlson, M; Cepko, C (2002)
The expression patterns of the transcription factor, Sox-9, and of the nuclear factor, cDachsund-2, were examined in the developing chick telencephalon. Both genes were expressed in the ventricular zone and in the subventricular zone of the telencephalon during the period of neurogenesis. Whereas Sox-9 was not expressed in postmitotic tissues, cDachsund-2 was specifically expressed in the neostriatum and in subdivisions of the hyperstriatum embryonically and in posthatch chicks.